2005
DOI: 10.1007/s11089-005-4818-y
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Disposition and Understanding Illness

Abstract: Although Dull and Skokan (1995) proposed a cognitive model of the effect of religion on health, they neglected to clearly identify the multi-dimensional nature of religion as a cognitive schema. The present paper identifies various aspects of spiritual disposition (defined as personality and beliefs) that can play a role in an individual's adaptation to illness. Specifically, this paper reviews the factors of religious doctrine and affiliation, spiritual beliefs, religious orientation, God locus of control, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 70 publications
1
16
0
4
Order By: Relevance
“…Some studies have confirmed the existence of a relationship between spirituality and physical health [1012]. Spiritual beliefs include the perception of a higher power and a sense of being connected to this source of power [11]. Some findings suggest that spiritually-inclined individuals adopt healthier methods of coping with psychological pressures, which in turn has a positive effect on their health.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have confirmed the existence of a relationship between spirituality and physical health [1012]. Spiritual beliefs include the perception of a higher power and a sense of being connected to this source of power [11]. Some findings suggest that spiritually-inclined individuals adopt healthier methods of coping with psychological pressures, which in turn has a positive effect on their health.…”
Section: Introductionmentioning
confidence: 99%
“…Religious coping strategies refer to the employment of the cognitive and behavioural techniques when faced with stressful situations, in individuals with religious principles (Tix and Frazier, 1998). In other words, through religious coping strategies, humans attempt to comprehend these stressful situations via their religious belief systems (Gall and Grant, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although considerable research has been conducted regarding R/S and cancer, there is no consensus in the literature as to the definitions of R/S. To date the role that R/S plays regarding an individual's psychological well-being and/or psychological distress is unclear [9].…”
Section: Introductionmentioning
confidence: 99%